The Coming of the Greeks - Grumach, E.
with Prefatory Note by S. Hood; I. Varying Opinions (2-9); II. Linguistic Evidence for Greek Intrusion into the Aegean at a Late Date (10-56); III. The History of the Dialects. Unter anderem gegen “Luviomania” (57).